I've won, no I've won, no I've won - Child, Lauren; Ingham, Dave.; Tiger Aspect Productions (New York : Grosset & Dunlap, 2006)
Lola wants to win every game against her older brother Charlie, even if it means making up creative shortcuts.
"Illustrations from the TV animation produced by Tiger Aspect"--T.p. verso.
"Text based on script written by Dave Ingham"--T.p. verso.
First published: Great Britain : Puffin Books, 2005.
1.6
K-3
Keywords: Brothers and sisters -- Juvenile fiction; Games -- Juvenile fiction; Brothers and sisters -- Fiction; Games -- Fiction; Games -- Fiction; Siblings -- Fiction